A rare case of a male infant with down-turner syndrome and review of cases - Salwati Shuib,; Bador KM,; Wan Noor Aida MI,; Siti Fairuz AR, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Individuals with double aneuploidy of Down-Turner syndrome are very rare and to date, fewer than 50 cases have been reported, worlwide. We report a case of a male infant who presented with dysmorphic features of upslanting eyes, flat nasal bridge, wide spaced nipples and macroglossia. Based on the clinical features, he was diagnosed with Down syndrome. His peripheral blood sample was taken and sent for cytogenetic analysis for confirmation. Chromosome analysis of his lymphocyte cell culture revealed a mosaic pattern of double aneuploidy with monosomy X identified in 31 metaphases and trisomy 21 in 14 metaphases: (45,X[31]/47,XY,+21[14]). Further analysis with fluorescence in situ hybridization (FISH) using Vysis LSI SRY Spectrum Orange/CEP X Spectrum Green Probe and Vysis CEP Y Spectrum Aqua Probe and Vysis LSI 21 Spectrum Orange Probe performed on the cells (nuclei and metaphases) has confirmed the presence of the abnormal two cell lines (81% monosomy X and 19% trisomy 21) in the patient. Ultrasound investigations of his pelvic region showed normal testes and no evidence of uterus, ovary or vagina. To the best of our knowledge, this is the first Down-Turner syndrome reported in Malaysia. In conclusion, this case demonstrates the importance of Giemsa-banded karyotype and FISH analyses as diagnostic tools in identifying the chromosomal abnormality and determining the ratio of the normal:abnormal cells present in the patient. An annotated bibliography of earlier reported cases of Down-Turner with documented karyotyping is also included in this report.